Post-Transcriptional Inflammatory Response to Intracellular Bacterial c-di-AMP - Mahmoud, Linah; Abdulkarim, Alaa S.; Kutbi, Shaima; Moghrabi, Walid; Altwijri, Sulaiman; Khabar, Khalid S. A.; Hitti, Edward G. (Frontiers in Immunology, 2020)
Cyclic-di-AMP (c-di-AMP) is a bacterial second messenger that is produced by intracellular bacterial pathogens in mammalian host macrophages. Previous reports have shown that c-di-AMP is recognized by intracellular pattern recognition receptors of the innate immune system and stimulate type I interferon response. Here we report that the response to c-di-AMP includes a post-transcriptional component that is involved in the induction of additional inflammatory cytokines including IL-6, CXCL2, CCL3 and CCL4. Their mRNAs contain AU-rich elements (AREs) in their 3'UTR that promote decay and repress translation. We show that c-di-AMP leads to the phosphorylation of p38 MAPK as well as the induction of the ARE-binding protein TTP; both components of a signalling pathway that modulate the expression of ARE- containing mRNAs at the post-transcriptional level. Pharmacological inhibition of p38 reduces the c-di-AMP-dependent release of induced cytokines, while TTP knockdown increases their release and mRNA stability. C-di-AMP can specifically increase the expression of a nano-luciferase reporter that contains AREs. We propose a non-canonical intracellular mode of activation of the p38 MAPK pathway with the subsequent enhancement in the expression of inflammatory cytokines. C-di-AMP is widely distributed in bacteria including infectious intracellular pathogens, hence, understanding of its post-transcriptional gene regulatory effect on the host response may provide novel approaches for therapy.